Konsep Pendidikan Karakter Pada Sekolah Inklusi Tingkat Usia Dasar - Rina Rahmi; Aswatun Hasanah; Septika Laily Anti (AR-RIAYAH : Jurnal Pendidikan Dasar, 2020)
This article aims to examine character education in primary age inclusion schools. Focus the discussion on research on the basic concepts of character education in inclusion schools, the process of character education planning in inclusion schools, how character education is implemented in inclusion schools, and how to monitor character education in inclusion schools. The approach used is a qualitative approach to library research. Data sources are obtained from books or journals relevant to this study. The data collection technique is to analyze character education in elementary age inclusion schools to obtain data from literature sources. Data analysis was conducted by examining the concept of character education in basic age inclusion schools using reference materials. The results of this study show that (1) character education planning in inclusion schools is carried out by meeting teacher work, socialization of all parties related to the school, and the preparation of a Learning Implementation Plan (RPP), (2) in the application of character education in inclusion schools through integrating in learning, self-development through school culture as habituation, as well as inclusion education (3) character education monitoring in inclusion schools including observation and direct mentoring , identify the obstacles that occur, make improvements from the constraints that occur, as well as measure the success of the implementation of character education programs. Inclusion education is done well because of the intertwining of cooperation and support from various parties to change the way of thinking in doing social tolerance and humanizing people